2014
DOI: 10.1037/a0035448
|View full text |Cite
|
Sign up to set email alerts
|

Shrugging it off: Does psychological detachment from work mediate the relationship between workplace aggression and work-family conflict?

Abstract: The current study investigates workplace aggression and psychological detachment from work as possible antecedents of work-family conflict. We draw upon Conservation of Resources theory and the Effort-Recovery Model to argue that employees who fail to psychologically detach from stressful events in the workplace experience a relative lack of resources that is negatively associated with functioning in the nonwork domain. Further, we extend prior research on antecedents of work-family conflict by examining workp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 77 publications
(118 reference statements)
2
87
0
3
Order By: Relevance
“…So far, only a few between‐person studies have explored the role of social stressors in psychological detachment from work. For instance, Demsky et al () found that (co‐worker and self‐reports of) workplace aggression was negatively associated with employee‐reported detachment.…”
Section: Stressors As Predictors Of Poor Psychological Detachmentmentioning
confidence: 99%
“…So far, only a few between‐person studies have explored the role of social stressors in psychological detachment from work. For instance, Demsky et al () found that (co‐worker and self‐reports of) workplace aggression was negatively associated with employee‐reported detachment.…”
Section: Stressors As Predictors Of Poor Psychological Detachmentmentioning
confidence: 99%
“…According to the resource investment principle of COR theory, the more resources individuals dispose of, the more likely they are to invest resources in order to gain additional resources and to protect themselves against future resource loss (Halbesleben et al, 2014). Research on recovery suggests that energetic resources are replenished when individuals experience high psychological detachment and sleep quality during periods of respite (Demsky, Ellis, & Fritz, 2014;Zijlstra et al, 2014). Psychological detachment, the mental disengagement from work during off-job time (Sonnentag & Fritz, 2015), preserves mental energy by suspending the mental occupation with work stressors.…”
Section: Practitioner Pointsmentioning
confidence: 99%
“…Accordingly, psychological detachment has been described to be a core recovery experience (Sonnentag & Fritz, 2015). It has been shown to be related to a range of other important health-, well-being-, and performance-related outcomes, including emotional exhaustion, work-family conflict, and work engagement (Demsky, Ellis, & Fritz, 2014;Fritz & Sonnentag, 2009;Fritz et al, 2010;Sonnentag, Binnewies, & Mojza, 2010). 1 Also sleep plays a key role in recovery processes (Querstret & Cropley, 2012;Sonnentag et al, 2008).…”
Section: Recovery From Workmentioning
confidence: 99%